Uso de herbicidas em unidades de conservação de São Paulo - Farias, Ana Beatriz de Sousa (Universidade Federal de São Carlos)
Protected areas (PAs) are essential for conserving native biodiversity and the ecosystem services they provide. In Brasil, these areas are governed by the National System of Nature Conservation Units (SNUC) and are classified into two main management groups: Strict Protection and Sustainable Use. Among the factors that compromise biodiversity conservation in PAs, the presence of invasive alien species stands out, as they represent one of the main drivers of biodiversity loss and directly affect the effectiveness of conservation and restoration efforts. One of the strategies used to control these species is the application of chemical methods, with herbicides being an efficient alternative. In this context, this research aims to (i) evaluate the use of herbicides in ecological restoration within protected areas in the state of São Paulo, (ii) determine whether legal restrictions exist regarding herbicide use in ecological restoration in these areas, and (iii) identify and quantify the protected areas in which herbicide use is permitted or prohibited for restoration purposes. In order to achieve the goals, the current environmental legislation and the management plans of each state-level PA were analyzed to verify permissions or restrictions regarding the use of chemical control. The results suggest that the lack of specific guidelines in management plans tends to affect how chemical control is implemented, leading to differences in how management actions are carried out. In this context, it is important that these documents incorporate more consistent technical guidance capable of better supporting decision-making by managers and promoting the adoption of efficient methods suited to the needs of each protected area.
Use of herbicides in conservation units in São Paulo
Keywords: Áreas protegidas; Conservação da biodiversidade; Controle químico; Invasões biológicas; Planos de manejo; Política pública; Restauração ecológica; Biodiversity conservation; Biological invasions; Chemical control; Ecological restoration; Management plans; Protected areas; Public politics; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; 13. Ação contra a Mudança Global do Clima